Prolonged QT Syndrome in a 27-Year-Old Female Presenting as a Cardiac Arrest after Elective Surgery - Aibek E. Mirrakhimov; Prakruthi Voore; Alaa M. Ali (Case Reports in Critical Care)
Cardiac arrest is a true medical emergency and clinicians should base the management on American Heart Association advanced cardiac life support algorithm. The potential triggers of cardiac arrest should be sought. We present a case of a 27-year-old female who developed cardiac arrest and was later found to have congenital long QT syndrome. The patient’s outcome was favorable. Discussion of the key management options will be discussed in the text.